Pengaruh Pengendalian Internal, Budaya Organisasi, Religiusitas, Dan Love of Money Terhadap Kecenderungan Kecurangan - Romadhon, Yeni Riski; Muhammad, Erfan; Hotimah, Enur (Jurnal Ekonomi Syariah Pelita Bangsa, 2024)
The purpose of this research is to obtain practical confirmation of the effect of internal control, organizational culture, religiosity, and love of money on the desire to commit fraud. This study was conducted at Pawnshops in the Madura area. The sample selection method used is purposive sampling. The main source of information in this study was obtained through the use of a questionnaire-based survey using a Likert scale, which was administered to the staff of the pawnshop, with 52 respondents participating. The study considered four independent variables: internal control, organizational culture, religiosity, and love of money, as well as one dependent variable: propensity to commit fraud. Data analysis was conducted using IBM SPSS 25 software. The research findings show that internal control, organizational culture, and religiosity each have a significant influence on fraud. However, love of money has no impact on cheating behavior. This is inferred from respondents' views which indicate that the urge to act unethically is not related to the love of money because money is not considered a symbol of personal success or a symbol of achievement that makes a person respected in society.